POTRET POLITIK PEMBANGUNAN EKONOMI KAMPUNG MAREDAN 2014-2016 - Anwar, Khairul (Nakhoda: Jurnal Ilmu Pemerintahan, 2017)
This study aims to describe the economic development of Maredan kampong 2014-2016. Thisresearch uses R.William Liddle (2004) conceptualization that is ?Restricted Pluralism?. Thispolitical analysis is included in the pluralist paradigm of modern political economy. In thisanalysis, research attempts to answer the main questions, such as whether Maredan villageeconomic development politics? This question is answered by identifying: (1) What are thepreference and preferences of building a penghulu? What is the position of the actor in thevillage development policy process? The results of this study revealed that The choice ofMaredan village development policy is determined by the actions of the village heads andinstitutions in linking the market and the will of the government as a manifestation of theinherent authority. The ability to ?reconcile? these two interests is the current policy of villagedevelopment in Maredan. There are many issues of governance and village development Thatappear on the surface. But the most prominent political color of economic development inMaredan is the economic factor that affects Maredan society.